SOLIDARITAS SOSIAL PADA TRADISI AYUN BUDAK SUKU MELAYU DI KOTA DUMAI PROVINSI RIAU - yana, rahmah husna; Triyanto, Triyanto; Juraida, Irma (Universitas Teuku Umar, 2024)
The tradition of swinging slaves is one of the intangible cultural heritages that is still preserved from generation to generation by the Melayu community in Dumai City, Riau Province. The practice of rocking a baby is not only limited to a physical act, but is also full of social and cultural meaning. However, along with social changes, solidarity in the Ayun Slave tradition has also undergone changes. By adopting Émile Durkheim's perspective, this research examines how factors such as urbanization, modernization and globalization influence the form and meaning of social solidarity in the Ayun Slave practice. This research was conducted through a descriptive qualitative approach. From the results of this research, it was found that the slave swinging tradition functions as a means of strengthening relationships between family members and society, and also as a medium for transferring cultural values from generation to generation. Slave swings also become a forum for people to share happiness and celebrate important moments in a child's life.Keywords: Social solidarity, Emile Durkheim, Ayun Budak.